Students’ perception toward English club activities - Zulvy Melviza; Syamsul Bahri Ys; Nira Erdiana (Universitas Syiah Kuala, 2017)
This study is intended to find out the perception of students toward English club activities in speaking. This study was conducted at SMAN 3 Banda Aceh. The researcher used two instruments to find the data needed, namely; questionnaire and interview. Both questionnaire which adapted from Kasmalinda (2011) and interview were used by the researcher to figure out the perception of students toward English club activities in practicing speaking. The researcher combined both of the instruments to support the data of the research. the sample of this study was the students of SMAN 3 Banda Aceh who have participated English club. The researcher took 40 students as the sample (all English club members). Based on the data obtained from both instruments used, the findings showed that students perceived English club plays an important role in supporting students to practice speaking. The students also think that English club has a great way to encourage students’ motivation to practice speaking with friends. The students also viewed that they feel glad while joinning English club. In other words, English club gets them more experiences and more knowledge. In addition, the class atmosphere tends to be fun and comfortable and it makes them more interested in practicing speaking.